AGE OF ZIRCONS FROM CHROMITES IN THE RESIDUAL OPHIOLITIC ROCKS AS A REFLECTION OF UPPER MANTLE MAGMATIC EVENTS - Savelieva G.N.; Suslov P.V.; Larionov A.N.; Berezhnaya N.G. (My University, 2006)
Geochronological dating of ophiolite rocks traditionally meets the following problems: (1) tectonic division of ophiolite complexes with subsequent juxta-position of rocks of different ages; (2) extremely low contents of radiogenic components in mantle residues of ultramafic rocks representing the earliest deepseated complexes of ophiolite sequences; and (3) the disturbance of Sm/Nd and Rb/Sr systems in the rock-forming clino- and orthopyroxenes of residual ultramafic rocks, making it impossible to date mantle rocks associated with plutonic and volcanosedimentary complexes in a single ophiolite association.
Keywords: Precambrian::Proterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский